Construction Of Death Penalty Legal Arrangements in Indonesia - RIYADI, Padlah (Indonesia Strategic Sustainability, 2023)
Purpose - This study aims to investigate and understand the construction of death penalty legal arrangements in Indonesia.Methodology - This study uses document analysis to examine various documents, such as texts, records, official reports, personal diaries, or historical documents, that provide valuable insights for this study. Findings - The issuance of capital punishment as the primary punishment became an alternative (exceptional) special punishment that is based on three main ideas. From the point of view of the objective of the death penalty punishment, in essence, it is not the main or main means to regulate, discipline and improve individuals or society. The death penalty is only a means of exception. So, the death penalty is likened to amputation or surgery in the medical field, which is not the main medicine but the last medicine. Second, the concept of capital punishment as a special punishment departs from the idea of mono-dualistic balance. This idea is oriented towards balancing public interest or protecting society and paying attention to individual interests or protection, with a probationary period of 10 years. Third, the maintenance of capital punishment, even though it is a special punishment, is also based on avoiding societal demands or reactions that are revengeful or extra-legal. Implication - This study has implications for policy, public awareness, comparative analysis, human rights advocacy, and future research directions. Its findings can contribute to informed decision-making, public discourse, and efforts to promote a more just and humane legal system.